PERANCANGAN ALAT PERAKIT RODA JARI-JARI SEPEDA MOTOR UNTUK MEMAKSIMALKAN PRODUKTIVITAS PEKERJA DENGAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) DAN VALUE ENGINEERING - Arif Hernanto (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2021)
The assembly of RADIUS wheels (spokes) motorcycle in the community using a wheel stand that does not support the maximum of its users. The Assembly with the seat position of the knee is below 45 º and the back position of 45 º to 65 º from the vertical field leads to the physical complaint of the finger wheel assemblers’ worker. For that it is necessary for the radius of the wheel-builder tool that can help fully assembly the wheel of the fingers with a better working method. The design of the fingertip-wheel builder is done using Quality Function Deployment (QFD) method to identify the needs of users, and Value Engineering (VE) method is used to select the tool concept with the highest value. Concept selection is done by considering the function values and cost of the concept. The results of the concept selection realized in the form of prototype to be tested tools to fit human body size. From the test obtained the results of the working position of the radius wheel assembly better than the previous and increased effectiveness of the assembly time of 33% (ordinary type) and 19% (custom type). Kata kunci: wheel builder tool, quality function deployment, value engineering.